ANALYSIS OF UJRAH RIGHTS FOR CUSTOMERS ON THE MURABAHAH BIL WAKALAH CONTRACT CLAUSE: Muamalah Fiqh Study - Alya Nesha Putri Zega; Azka Amalia Jihad (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study aims to analyse the right of ujrah for customers under the murabahah bil wakalah contract clause, from the perspective of fiqh muamalah and sharia economic law in Indonesia. Murabahah bil wakalah is a financing scheme that is widely used in Islamic banking, but in practice, there are still problems related to the charging of ujrah that are not always clearly separated from the margin of murabahah. This study uses a normative juridical method with a statutory and conceptual approach, drawing on the DSN-MUI fatwa, the Compilation of Sharia Economic Law (KHES), Law Number 21 of 2008 concerning Sharia Banking, as well as classical and contemporary muamalah fiqh doctrines. The results of the study show that the imposition of ujrah in the murabahah bil wakalah contract is justified under sharia as long as it is treated as a reward for wakalah services, agreed in advance, separated from the murabahah margin, and carried out in accordance with the principles of justice and transparency. This research is expected to make a normative contribution to strengthening sharia financing practices that are fair, transparent and in accordance with sharia principles.